The Urgency of Reforming Indonesian Commercial Law in Facing Digital Trade - Ahmad Baqi; Nasyfah Salsabila Harahap (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
The development of digital technology has significantly changed trade patterns in Indonesia, marked by the emergence of e-commerce, fintech, and the platform-based economy. However, this progress has not been matched by adequate legal preparedness. Indonesian trade law still relies heavily on the Commercial Code (KUHD), which was historically designed for conventional transactions, thus failing to accommodate the complexities of digital transactions. This study aims to analyze the current state of trade law, identify normative limitations, and examine the urgency of legal reform in the face of digitalization. The method used is a qualitative approach through a literature review analyzing various regulations such as the KUHD, the ITE Law, and the Consumer Protection Law. The results indicate a gap in norms related to electronic contracts, click-wrap agreement mechanisms, digital platform liability, personal data protection and online dispute resolution. Furthermore, legal relationships in digital transactions involving third parties, such as marketplaces, add to the complexity and have not been comprehensively regulated. This situation has the potential to create legal uncertainty and weaken protection for consumers and businesses. Therefore, adaptive and integrative normative reform of trade law is needed to create legal certainty, justice, and effective protection in the digital trade ecosystem in Indonesia. This update is expected to be able to answer the challenges of the digital era while supporting sustainable national economic growth.